Global Insights on Public Perceptions and Engagement based on TikTok politics - Devi, Indah Kartika; Sinduwiatmo, Kukuh (Universitas Muhammadiyah Sidoarjo, 2024)
In the digital era, social media platforms like TikTok are increasingly used for political campaigns. This study examines the PAN party's use of the viral TikTok song